Association of Early Life Adversity, Perceived Socioeconomic Status, Parental Education, and Anger among Urban Indian Youth - Sonia Suchday; Anthony F. Santoro; Natasha Ramanayake; Maureen Almeida (Indian Journal of Social Psychiatry)
Background: Anger is disruptive to society requiring close regulation, particularly in collectivist cultures such as India. Circumstances such as socioeconomic status, early life adversity (ELA), and parental education influence the experience/expression of anger. Objectives: The current study assessed associations between ELA and subjective socioeconomic status (SSS), parental education, and anger and anger regulation among urban Indian college students in Mumbai. It was predicted that ELA would predict anger after controlling for SSS and parental education. Materials and Methods: Self-reports on measures of adversity before the age of 16 years, parents’ education, subjective SSS (MacArthur SES Ladder), and measures of anger (Anger Rumination Scale, Spielberger trait anger, anger expression, and anger suppression) were collected from participants recruited from a college in South Mumbai, India. Association among the variables was assessed using Pearson’s correlation analysis. Stepwise regression analysis was computed to predict anger while controlling for age, gender, and parental education/subjective status. Results: ELA was associated with trait anger (r = 0.17, P < 0.01), anger suppression (r = .25, P < 0.01), expression (r = 0.15, P < 0.01), and rumination (r = 0.26, P < 0.01), and ELA remained a significant predictor of all anger dimensions, controlling for SSS and parental education. Conclusion: These data indicate that ELA leads to elevated anger, anger rumination, and its expression and suppression.